PENERAPAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN PARTISIPASI BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMA - I Made Ary Yustikanatha Wirjana; I Wayan Sumandya (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Teaching at the right level (TaRL) is a learner-centered learning approach in which students are grouped into groups with a certain cognitive level. This research aims to determine the application of teaching at the right level (TaRL) can increase students' participation in learning mathematics at SMA Negeri 2 Tabanan. This type of research is Classroom Action Research (CAR), using the cycle design from Kemmis & Mc Taggard. The location of this research is SMA Negeri 2 in class XI MIPA 3 with 35 students as research subjects. Based on the results of the study, the results obtained were the application of teaching at the right level (TaRL) increased students’ participation where in the pre-cycle of student participation there was a percentage of 22.14% in the low category, in cycle I the percentage of students’ participation increased to 54.11% got the medium category and in cycle II it increased to 81.07% in the very high category. So that the application of teaching at the right level (TaRL) increases students’ participation in class XI MIPA 3 at SMA Negeri 2 Tabanan